METHODOLOGICAL AND METHODICAL BASIS OF THE NETWORK APPROACH TO THE STUDY OF SOCIAL IDENTIFICATION - P. P. Deriugin; I. A. Baruzdin; S. V. Kurapov (Дискурс)
The article is devoted to the compilation and analysis of existing methodological approaches to research of the process of social identification in the philosophical and sociological science. The characteristics of the process of social identification are revealed on philosophical and sociological level. The history of the formation of the concept of identity, a brief review of the ideas associated with the study of identity in the areas of philosophy and psychology is considered. The approaches to the research of the identification process in different schools and directions of sociology are considered. The major sociological aspects of studying an identification problem among the Russian youth are identified. The heuristic network method to study identification revealed the benefits of its axiological direction. The effect of values on the identification choice of today's youth is indicated.